Nuclear Medicine and Radiologic Imaging in Sports Injuries - Glaudemans, Andor W.J.M; Dierckx, Rudi A.J.O; Gielen, Jan L.M.A; Zwerver, Johannes (Hans) (Springer eBooks, 2015)
This comprehensive book describes in detail how nuclear medicine and radiology can meet the needs of the sports medicine physician by assisting in precise diagnosis, clarification of pathophysiology, imaging of treatment outcome, and monitoring of rehabilitation. Individual sections focus on nuclear medicine and radiologic imaging of injuries to the head and face, spine, chest, shoulder, elbow and forearm, wrist and hand, pelvic region, knee, lower leg, ankle, and foot. The pathophysiology of sports injuries frequently encountered in different regions of the body is described from the perspective of each specialty, and the potential diagnostic and management benefits offered by the new hybrid imaging modalities - SPECT/CT, PET/CT, and PET/MRI - are explained. In addition, a range of basic and general issues are addressed, including imaging of the injuries characteristic of specific sports. It is hoped that this book will promote interdisciplinary awareness and communication and improve the management of injured recreational or elite athletes.